Understanding and controlling water stability of MOF-74. Issue 14 (18th March 2016) - Zuluaga, Sebastian; Fuentes-Fernandez, Erika M. A.; Tan, Kui; Xu, Feng; Li, Jing; Chabal, Yves J.; Thonhauser, Timo
Abstract : The H2 O → OH + H reaction poisons the metal centers and starts the degradation of the crystal structure of MOF-74. Abstract : Metal organic framework (MOF) materials in general, and MOF-74 in particular, have promising properties for many technologically important processes. However, their instability under humid conditions severely restricts practical use. We show that this instability and the accompanying reduction of the CO2 uptake capacity of MOF-74 under humid conditions originate in the water dissociation reaction H2 O → OH + H at the metal centers. After this dissociation, the OH groups coordinate to the metal centers, explaining the reduction in the MOF's CO2 uptake capacity. This reduction thus strongly depends on the catalytic activity of MOF-74 towards the water dissociation reaction. We further show that—while the water molecules themselves only have a negligible effect on the crystal structure of MOF-74—the OH and H products of the dissociation reaction significantly weaken the MOF framework and lead to the observed crystal structure breakdown. With this knowledge, we propose a way to suppress this particular reaction by modifying the MOF-74 structure to increase the water dissociation energy barrier and thus control the stability of the system under humid conditions.